2022
DOI: 10.1186/s00015-022-00414-z
|View full text |Cite
|
Sign up to set email alerts
|

Glaciofluvial sequences recording the Birrfeld Glaciation (MIS 5d–2) in the Bern area, Swiss Plateau

Abstract: In this paper, we document that glaciofluvial gravel sequences and glacial till deposits that are exposed in the Müntschemier and Finsterhennen gravel pits (Swiss Plateau west of Bern) record three glacial advances during the Birrfeld Glaciation, which corresponds to the last glacial cycle. Sedimentological logging shows that both gravel pits expose deposits of glaciofluvial braided river systems. These sediments are overlain by a till that was deposited during the Last Glacial Maximum (LGM). The results of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The grain shapes are furthermore independent of the lengths of the b-axes. Moreover, the axes' ratios of the coarse-grained material used in this study are similar to those reported for Alpine conglomerate beds (Tanner, 1944;Haldemann, 1948;Bürgisser, 1980), most likely because parts of the material in the gravel pit was derived from these (Pfander et al, 2022).…”
Section: Influence Of Particle Shape Outcrop Orientation and Grain Oc...supporting
confidence: 83%
See 4 more Smart Citations
“…The grain shapes are furthermore independent of the lengths of the b-axes. Moreover, the axes' ratios of the coarse-grained material used in this study are similar to those reported for Alpine conglomerate beds (Tanner, 1944;Haldemann, 1948;Bürgisser, 1980), most likely because parts of the material in the gravel pit was derived from these (Pfander et al, 2022).…”
Section: Influence Of Particle Shape Outcrop Orientation and Grain Oc...supporting
confidence: 83%
“…For these Quaternary deposits, measurements of cross-bed orientations and alignments of imbricated clasts revealed a paleoflow direction towards the N-NE (Fig. 2a; Pfander et al, 2022). We collected grain size data from eight locations that have four different orientations relative to the paleoflow direction (Fig.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations